Effect of a Plyometric Training Program on the Physical Parameters of ADHD Children: Behavioral and Cognitive Consequences - Hattabi, Soukaina; Bouallegue, Meher; Mhenni, Thouraya; Halouani, Jamel; Chtourou, Hamdi (International Journal of Sport Studies for Health, 2021)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopment disorder with inappropriate levels of inattention and hyperactivity/impulsivity that emerge during preschool-age causing several impairement that should be supported.Objectives: The purpose of this research was to explore the repercussion of plyometric training protocol (PT) on disruptive behavior and executive control among children with ADHD.Methods: Executive functions and ADHD related behaviors are assessed by graded tests before and after a 12-week PT (plyometric training) or NPT (did not perform PT training).Results: Findings show that participation in PT enhances behavior reports by parents and teachers (P < 0.001) and level of executive function (P < 0.001).Conclusions: These findings suggest that PT may improve positively ADHD symptomatology.